Моя Африка: поэма / Б. П. Корнилов - Корнилов Б. П. (Советский писатель, 1963)
Экземпляры: КХ (20111121) / Инвентарный номер: 0134134 / Цена: 0.12 / Сис.шифр: Р2 / Авт.знак: К 67 / ГРНТИ: 17 / ББК: 84(2)